Retrospective investigation of the 2019 African swine fever epidemic within smallholder pig farms in Oudomxay province, Lao PDR - Matsumoto, Nina; Siengsanan-Lamont, Jarunee; Halasa, Tariq; Young, James R.; Ward, Michael P.; Douangngeun, Bounlom; Theppangna, Watthana; Khounsy, Syseng; Toribio, Jenny-Ann L. M. L.; Bush, Russell D.; Blacksell, Stuart D. (Frontiers in Veterinary Science, 2023)
The 2019 African Swine Fever (ASF) outbreak in the Lao People's Democratic Republic (Lao PDR or Laos) represented a major epidemiologic event where a transitioning lower-middle income nation (LMIC) experienced a viral epidemic in a naïve pig population. The diversity of pig management styles creates challenges for local and regional policymakers when formulating recommendations to control an ASF outbreak. The aim of this study were to investigate the management of pigs in villages of Oudomxay province that were affected by ASF in 2019, as a case study in a smallholder pig-rasing system in northern Laos. The frequencies of well known risk factors were measured in the affected villages and the timelines and household level stock losses due to the outbreak were investigated. These findings were compared to data available from a similar outbreak in the southern province of Savannakhet. Disease control implications of these findings are discussed.Mean losses were 3.0-23.3 pigs per household, with a mean lost herd value of USD 349, 95% CI (294-415). These pig losses reflect those estimated in Savannakhet (6.7 pigs per household). However, the financial loss estimated per household was higher, USD 349 versus USD 215, possibly due to higher pig values and a higher input/output management approach in Oudomxay. The investigation revealed the presence of numerous ASF risk factors, such as swill-feeding and freeranging. In addition, poor biosecurity practices − such as inappropriate garbage disposal and slaughtering − that could contaminate the environment were present. ASF cases occurred across all villages between June and December 2019, with outbreak periods ranging from 22-103 days. These values are consistent with the outbreak in Savannakhet; however, notable differences in management styles were observed. These findings demonstrate the need for more disease control resources from the village to the Governmental level. Villages need support in enacting context appropriate biosecurity measures, whilst the ongoing surveillance and investigation of ASF require investment in logistical and veterinary resources at the Governmental level.